(untitled) (Journal of Informatics Education and Research, 2025)
In the context of Education 5.0, this study discusses the critical role that artificial intelligence plays in enabling individualized education for students with special needs. The main goal is to investigate how AI-powered educational technologies affect learning pathway customization and encourage active participation from students with special needs, particularly in peer-to-peer learning settings. The research uses a qualitative case study analysis and is based on a thorough evaluation from the major meta-databases such as IEEE Xplore, Web of Science (WOS), and Scopus. The results highlight how AI-enabled platforms, such as assistive technology and adaptive learning systems, allow for data-driven instructional modifications and real-time tailoring, catering to a variety of cognitive and socioemotional profiles. Furthermore, by removing obstacles to participation, the incorporation of augmented intelligence through AI-driven peer collaboration promotes inclusivity and emotional well-being in addition to improving academic results. Namely, the study highlights a research gap for statistically sound information as well as more thorough on-site assessments of AI-assisted peer-to-peer learning models. The ramifications highlight how important it is for educators, tech-developers, and legislators to work together in the 21st century to create and thoroughly evaluate AI systems that support equitable, connected, and interesting learning opportunities for students with special needs.